DUKUNGAN VENEZUELA TERHADAP PERJUANGAN PALESTINA (2009-2014) - Novriana, Shally; Fachri, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is political economy study which the background is solidarity action, whose the actors are nation. Nowadays many nations start the diplomatik relation or bilateral cooperation just because of the national interest and needs. However this phenomenon didn’t happen in relation between Venezuela and Palestinian. Diplomatik relation between both of these nation started by sympathy feeling of socialist nation, Venezuela. Venezuela’s Government, Hugo Chaves concern about the struggle of Palestinian who attacked by Israeli during twenty two days on January 2009, it named Operation Cast Lead. Palestinian have been force for along time, life under the monopoly of political economy by Israeli, and Israeli takes some districts of Palestinian region too.This research is conducted by using the research methods literature where the data and information received from sources that are relevant to the research problem. This research use constructivist perspective, solidarity concept and modernization theory to analyze the relationship and solidarity phenomenon between Venezuela and Palestinian.Venezuelan and Palestinian have the same history and similarity emotional, it makes Venezuelan’s President Hugo Chaves did solidarity act in political, economy and social to solve and help the struggle of Palestinian. Even if Hugo Chaves was died, solidarity act for Palestinian never ever stop, the new President, Nicolas Maduro still gave many aid in political, economy and social act.Keywords : solidarity, struggle, aid, political economy